Avaliação da resistência de híbridos simples de milho pipoca à Spodoptera frugiperda (J. E. Smith, 1797) - Crubelati, Náyra Cristiane de Souza (2010)
The use of resistant genotypes is important for integrated pest management and is being appreciated in plant breeding. The popcorn culture is quite similar to maize common, especially in relation to the occurrence of pest. For both cultures the caterpillar fall armyworm (Spodoptera frugiperda) (J. E. Smith, 1797) (Lepidoptera: Noctuidae) is a pest that causes major economic losses. However, the basis of the impact of pests on popcorn cultivation are rare, so estabilish necessary the study of possible simple hybrids as their resistance. In this experiment, were tested 36 simple hybrids of partial diallel and four commercial hybrids, in relation to damage caused by S. frugiperda under field conditions with natural infestation. The experiment design was a randomized block design, with four replications. The evaluations were carried out with a damage visual scale (adaptated of Davis & Williams, 1989). After the closing of the culture cycle assessments have been carried yield and for popping expansion. Later the diallel analysis was carried out in order to select the best hybrids to compare organic development and utilization of food by caterpillars S. frugiperda. In this analysis were selected nine hybrids and to compose the laboratory experiment were used two commercial hybrids with known features, IAC 112 and JADE. The experiment was in 10 repetitions by treatment (hybrid) and the data of this experiment were subjected to analysis of variance and then averages were compared by Scott-Knott test (pmenor0.05). The data analysis reported that the hybrids UEM-3, UEM-5, UEM-7 e IAC 112 are more resistant and hybrids UEM-2, UEM-4 e JADE are more susceptible.